Effects of melting and heat generation/absorption on unsteady Falkner-Skan flow of Carreau nanofluid over a wedge. (July 2017) - Khan, M.; Azam, M.; Alshomrani, A.S.
Highlights: Unsteady Falkner-Skan flow of Carraeu nanofluid over a wedge is modeled. Melting heat transfer is considered. Brownian motion and thermophoresis are accounted. Heat generation/absorption is incorporated. Zero nanoparticle mass flux condition is implemented. Abstract: This article focuses on the numerical investigation of the melting and heat generation/absorption phenomena in unsteady Falkner-Skan wedge flow of Carreau nanofluid. A zero nanoparticle mass flux condition at the boundary is implemented. Flow is induced due to stretched surface in the presence of the Brownian motion and thermophoresis effects. Suitable transformations are utilized to attain non-linear ordinary differential equations. The resulting non-linear ordinary differential equations are then solved numerically through bvp4c Matlab package. Effects of several emerging parameters on the temperature and nanoparticles concentration profiles are explored and discussed. The reduced Nusselt number is also calculated and examined. A comparison is presented between the current results and available data and found to be in outstanding agreement. Our study predicts that the temperature and nanoparticles concentration profiles depreciate by enhancing values of the melting parameter both for shear thinning and shear thickening fluids.